Steller Sea Lion (Eumetopias jubatus) Response to Non-lethal Hazing at Bonneville Dam - Tidwell, Kyle S.; Carrothers, Brett A.; Blumstein, Daniel T.; Schakner, Zachary A. (Frontiers in Conservation Science, 2021)
Protected Steller sea lions (Eumetopias jubatus) aggregate at Bonneville Dam on the Columbia River and prey upon multiple species of endangered salmon ascending the river. For more than 40 years, hazing has been employed to deter sea lions from such predation, but the response of sea lions is hazing through time is not well documented. We observed the behavior of Steller sea lions in periods with and without hazing during two spring Chinook salmon passage seasons to evaluate: 1) what effect hazing had on the number of animals present and their foraging behavior, and 2) whether they habituated to hazing. We found that hazing temporarily reduced the number of Steller sea lions, but only when actively hazed. During hazing, Steller sea lions were more likely to move away from hazers on the dam, decreased their foraging, and increased their time investigating the environment. However, these effects were temporary; their behavior returned to initial observation levels once hazing ceased. Furthermore, their responsiveness to hazing declined throughout the season, indicating habituation and raising concern for the application and long-term efficacy of hazing in managing predation on endangered salmon.